The 'Jedward' versus the 'Mohawk': a prospective study on a paediatric distraction technique. Issue 4 (29th April 2013) - Fogarty, Eoin; Dunning, Eilis; Koe, Stanley; Bolger, Turlough; Martin, Ciara
Abstract : Objective: To examine the use of a standard hospital glove, inflated as a balloon with a face drawn on it, as a distraction technique in children with an acute injury. Methods: We designed a study to assess the 'best' way to orientate the glove when drawing a face on it. A prospective study was performed in the authors' institution, where all children between the ages of 2 and 8 years presenting during the study period were given the option of playing with one of two glove balloons with a face drawn on it in two different ways. Results: 149 paediatric patients were assessed, of whom 136 picked a glove, 75 picked the 'Jedward' version and 61 the 'Mohawk' version. Conclusions: A standard hospital glove, inflated as a balloon with a face drawn on it, is a useful distraction for children with an acute injury. The face drawn should be drawn 'Jedward' style.